2019
DOI: 10.1152/ajplung.00417.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific airway hyperreactivity and sex-specific transcriptome remodeling in neonatal piglets challenged with intra-airway acid

Abstract: Acute airway acidification is a potent stimulus of sensory nerves and occurs commonly with gastroesophageal reflux disease, cystic fibrosis, and asthma. In infants and adults, airway acidification can acutely precipitate asthma-like symptoms, and treatment-resistant asthma can be associated with gastroesophageal reflux disease. Airway protective behaviors, such as mucus secretion and airway smooth muscle contraction, are often exaggerated in asthma. These behaviors are manifested through activation of neural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 77 publications
(109 reference statements)
1
28
0
Order By: Relevance
“…We previously reported that intra-airway acid induces mucus obstruction in the small airways (22). Similar to our previous studies, we found that intra-airway acid induced airway obstruction under both basal ( Figure 3A-3D) and methacholine-stimulated conditions ( Figure 3E-H).…”
Section: Diminazene Aceturate Reverts Acid-induced Mucus Obstruction supporting
confidence: 91%
See 4 more Smart Citations
“…We previously reported that intra-airway acid induces mucus obstruction in the small airways (22). Similar to our previous studies, we found that intra-airway acid induced airway obstruction under both basal ( Figure 3A-3D) and methacholine-stimulated conditions ( Figure 3E-H).…”
Section: Diminazene Aceturate Reverts Acid-induced Mucus Obstruction supporting
confidence: 91%
“…Studies were performed by individuals blinded to treatment; only an animal ID was associated with post-mortem samples. Our previous work for histological scoring indicated a "n" of 8 per sex was required to achieve statistical significance (22,35). We observed no sex differences in airway obstruction induced by acid and therefore combined male and female data.…”
Section: Methodsmentioning
confidence: 49%
See 3 more Smart Citations